2014
DOI: 10.1017/s1368980013003467
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational differences in acculturation experiences, food beliefs and perceived health risks among refugees from the Horn of Africa in Melbourne, Australia

Abstract: Objective: To investigate the differences in acculturation experiences between parent and adolescent refugees from the Horn of Africa in Melbourne, Australia and to explore food beliefs and perceived health risks from an intergenerational perspective. Design: Qualitative cross-sectional study involving a combination of semi-structured one-on-one interviews and focus group discussions. Setting: North-West suburbs of Melbourne, Australia. Subjects: Eritrean, Ethiopian, Somali and Sudanese refugees. Results: Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 34 publications
6
65
0
3
Order By: Relevance
“…Interestingly, African immigrant mothers in Australia reported that they wanted to try and maintain their traditional foods because their children were so drawn to junk food, yet often found it hard to do with their children. In fact, they reported using junk foods of the new country as a reward for eating their traditional foods [47]. It is also possible that mothers with a high demanding/high responsive style who have been in the U.S. for more than 5 years have acculturated into a different food environment where they demand less healthy foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, African immigrant mothers in Australia reported that they wanted to try and maintain their traditional foods because their children were so drawn to junk food, yet often found it hard to do with their children. In fact, they reported using junk foods of the new country as a reward for eating their traditional foods [47]. It is also possible that mothers with a high demanding/high responsive style who have been in the U.S. for more than 5 years have acculturated into a different food environment where they demand less healthy foods.…”
Section: Discussionmentioning
confidence: 99%
“…Parents may continue to maintain values, norms, and behaviors of their culture of origin while children may embrace the cultural attitudes and behaviors of the host country more quickly [46]. In relation to their diets Renzaho for example found that children of immigrants preferred Australian foods (i.e- energy dense snack foods) because they wanted to fit in with their peers and as a result their parents tried to control their dietary intake in hopes of retaining their traditional eating habits [47]. Unfortunately there is little evidence to understand this complex dynamic among immigrant children and parents in the US although a recent study found that children of non-US born parents had unhealthier dietary behaviors while the parents had several obesity protective behaviors [48] suggesting differential effects of an “obesogenic” environment on parents and children.…”
Section: Introductionmentioning
confidence: 99%
“…Youth think that health problems related to unhealthy lifestyle are long-term outcomes and still they are young and probably consider themselves impervious to them "it won't happen to me" [37,38]. However, students were able to clearly define healthy food and lifestyle but in practice their behaviors and food choices reflect that knowledge alone does not bring about change [3,8,37].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is associated with the beginning of independence and relative freedom from parental supervision, as well as the formation of new peer groups (Sylow & Holm, 2009). Some studies (Tiedje et al, 2014;Wilson & Renzaho, 2015) have reported intergenerational attitudinal differences towards eating among migrants. For adolescents and young adults in general, abstract, future-oriented health problems are of little significance, and eating behaviour remains 'present-oriented' (Al-Khamees, 2009;Collins, 1993).…”
Section: Pushpa 37 Years (Malayali Christian)mentioning
confidence: 99%